2015
DOI: 10.3390/polym7050921
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-cyclodextrin-Based Star Block Copolymers with Thermo-Responsive Behavior

Abstract: Star polymers are one example of three-dimensional macromolecules containing several arms with similar molecular weight connected to a central core. Due to their compact structure and their enhanced segment density in comparison to linear polymers of the same molecular weight, they have attracted significant attention during recent years. The preparation of block-arm star copolymers with a permanently hydrophilic block and an "environmentally" sensitive block, which can change its nature from hydrophilic to hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The tetra‐armed star‐shaped styrenic copolymers having pyrene side groups [ (S1‐S3)‐Pyr ] were prepared using core‐first approach (Scheme ), by which the number of arms of the star polymer could be clearly defined and would be equal to the number of the functional units on the polymerization‐initiating compound . Besides, this method provides good control on the macromolecular architecture . The tetra‐functional initiator ( 2 ) was synthesized via facile esterification and atom transfer radical addition reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The tetra‐armed star‐shaped styrenic copolymers having pyrene side groups [ (S1‐S3)‐Pyr ] were prepared using core‐first approach (Scheme ), by which the number of arms of the star polymer could be clearly defined and would be equal to the number of the functional units on the polymerization‐initiating compound . Besides, this method provides good control on the macromolecular architecture . The tetra‐functional initiator ( 2 ) was synthesized via facile esterification and atom transfer radical addition reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclodextrin allows for unusually high grafting densities as for typical well-defined multiarm initiators. Primarily, 7, 58,109 Fig . 6 The two most common approaches in preparation of CD-based monomers.…”
Section: Incorporation Of Initiator Groups For Multiarm Polymersmentioning
confidence: 99%
“…B: Copper mediated azide-alkyne coupling. Polymer Chemistry Review 14 58,110 or 21 23,64 sites are accessible but intermediate numbers were also reported. 111,112 Arms not directly involved in the polymerisation can be further modified to tailor the solubility of the initiator or attach various pendants such as sugars.…”
Section: Incorporation Of Initiator Groups For Multiarm Polymersmentioning
confidence: 99%
“…More importantly, it is easy to form unimolecular micelle, which demonstrates a micellar behavior as a single molecule, avoiding dissociation of the micelle under dilution. Among multiarmed star copolymers, cyclodextrin (CD)‐core star copolymers are very interesting and important candidate drug carriers for drug delivery . This is because a CD‐core star polymer shows a designable and well‐defined molecular architecture, but its synthesis procedures is less tedious compared with that of a dendritic polymer.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10,[16][17][18][19][20][21][22][23][24][25][26][27][28] This is because a CD-core star polymer shows a designable and well-defined molecular architecture, but its synthesis procedures is less tedious compared with that of a dendritic polymer. Through structure control, β-CD-core star polymers with 7, 14, or 21 arms could be synthesized accurately, especially after controlled/living radical polymerization and click reaction techniques were used, [9,10,[16][17][18][19][20][21][22][23][24][25][26][27][28] However, so far drug delivery systems based on CD-core star copolymers were obtained by multimolecular selfassembly, [16][17][18][19][20][21] or formation of unimolecular micelles with the help of an organic solvent. [9,10,28] There are few reports on drug-encapsulated CD-core star polymeric system, which could directly dissolve in aqueous solution without the help of an organic solvent.…”
Section: Introductionmentioning
confidence: 99%